Improved solutions for ill-conditioned problems involved in set-membership estimation for fault detection and isolation. (October 2017) - Ravanbod, Laleh; Jauberthie, Carine; Verdière, Nathalie; Travé-Massuyès, Louise
Highlights: A bounded-error framework is considered. A procedure to improve the estimation of derivatives from noisy signals is proposed. A procedure to solve linear interval equation systems is given. A FDI algorithm is developed based on the two previous items. Abstract: Set-membership (SM) estimation implies that the computed solution sets are guaranteed to contain all the feasible estimates consistent with the bounds specified in the model. Two issues often involved in the solution of SM estimation problems and their application to engineering case studies are considered in this paper. The first one is the estimation of derivatives from noisy signals, which in a bounded uncertainty framework means obtaining an enclosure by lower and upper bounds. In this paper, we improve existing methods for enclosing derivatives using Higher-Order Sliding Modes (HOSM) differentiators combining filtering. Our approach turns the use of high order derivatives more efficiently especially when the signal to differentiate has slow dynamics. The second issue of interest is solving linear interval equation systems, which is often an ill-conditioned problem. This problem is reformulated as a Constraint Satisfaction Problem and solved by the combination of the constraint propagation Forward Backward algorithm and the SIVIA algorithm. The two proposed methods are tested on illustrative examples. The two methods are then used in a fault detection and isolation algorithm based on SM parameter estimation that is applied to detect abnormal parameter values in a biological case study.